Sometimes-Competing Retrieval (SOCR): A Formalization of the Comparator Hypothesis - Stout, Steven C; Miller, Ralph R (Psychological review, 2007)
Cue competition is one of the most studied phenomena in associative learning. However, a theoretical disagreement has long stood over whether it reflects a learning or performance deficit. The comparator hypothesis, a model of expression of Pavlovian associations, posits that learning is not subject to competition but that performance reflects a complex interaction of encoded associative strengths. That is, subjects respond to a cue to the degree that it signals a change in the likelihood or magnitude of reinforcement relative to that in the cue's absence. Initially, this performance-focused view was supported by studies showing that posttraining revaluation of a competing cue often influences responding to the target cue. However, recently developed learning-focused accounts of retrospective revaluation have revitalized the debate concerning cue competition. Further complicating the picture are phenomena of cue facilitation, which have been addressed less frequently than cue competition by formal models of conditioning of either class. The authors present a formalization and extension of the comparator hypothesis, which results in sharpened differentiation between it and the new learning-focused models.